Conceptual framework of internal Sharīʿah audit effectiveness factors in Islamic banks - Latifah Algabry; Syed Musa Alhabshi; Younes Soualhi; Omar Alaeddin (ISRA International Journal of Islamic Finance, 2020)
Purpose: The main Purpose: of this research is to figure out the most effective determinants that play a vital role in enhancing the effectiveness of the internal Sharīʿah audit in the Islamic banking industry. Design/methodology/approach This paper reviews the existing literature to build comprehensive knowledge that would assist in determining the main factors that impact on the effectiveness of Sharīʿah audit in Islamic banks. Findings This research proposes a conceptual framework of factors that impact on Sharīʿah audit effectiveness in IBs based on previously published studies. The proposed framework includes external and internal factors as well as internal Sharīʿah audit structure, process and requirements. Practical implications First, the regulators need to provide a detailed framework for Sharīʿah audit which covers the main requirements for effective Sharīʿah governance. Second, Islamic financial institutions (IFIs) need to pay more attention to following the Sharīʿah audit process in order to achieve the objective of effective Sharīʿah governance. Finally, the dearth of empirical research on the role and effectiveness of Sharīʿah audit in Islamic banking highlights the need to develop an appropriate methodology to enhance the study of the effectiveness of Sharīʿah governance practices. Originality/value The Sharīʿah ensures compliance with its rules and regulations and enhances the soundness and credibility of the Islamic finance industry. This study identifies a number of issues that require further investigation in order to establish a better system of Sharīʿah audit and to identify the factors that affect Sharīʿah auditing practices. This paper is unique in covering the main elements that have influence on the effectiveness of Sharīʿah audit and proposes them in one framework.
Keywords: 330; Internal audit; Islamic banking; Sharīʿah audit; Sharīʿah governance